2022
DOI: 10.1200/go.21.00339
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on Patterns of Care and Outcome of Head and Neck Cancer: Real-World Experience From a Tertiary Care Cancer Center in India

Abstract: PURPOSE The COVID-19 pandemic has caused unprecedented health, social, and economic unrest globally, particularly affecting resource-limited low-middle–income countries. The resultant curfew had made the access to and delivery of cancer care services an arduous task. We have reported the patterns of care and 1-year outcome of head and neck squamous cell carcinoma (HNSCC) treatment before and during COVID-19 lockdown at our institution. MATERIALS AND METHODS Patients who underwent radiation therapy (RT) for non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…However, our cancer network serves 2.4 million people or 46% of the national population, meaning that our data is likely to be representative of national trends. The immediate impact of the reallocation of healthcare provision and COVID‐19 public health measures internationally on HNC stage at diagnosis is remarkably consistent, with the studies comparing the 2019 and 2020 cohorts described above being carried out in 13 different countries from North America, Europe, Australia and Asia 5,10–21 . The time periods evaluated in our study coincide with the most severe COVID‐19 public health measures being eased in many countries, not just our own 25 .…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…However, our cancer network serves 2.4 million people or 46% of the national population, meaning that our data is likely to be representative of national trends. The immediate impact of the reallocation of healthcare provision and COVID‐19 public health measures internationally on HNC stage at diagnosis is remarkably consistent, with the studies comparing the 2019 and 2020 cohorts described above being carried out in 13 different countries from North America, Europe, Australia and Asia 5,10–21 . The time periods evaluated in our study coincide with the most severe COVID‐19 public health measures being eased in many countries, not just our own 25 .…”
Section: Discussionsupporting
confidence: 85%
“…Of these studies, 16 (70%) reported that patients did not present with more advanced disease during the pandemic in 2020. 5 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 Furthermore, analysis of national cancer registry data showed that the incidence of HNC during 2020 was similar to what was observed in 2019, was in line with long term trends, and that patients were not presenting with more advanced disease during the pandemic. 22 Our study reinforces these findings but also indicates that the pandemic is unlikely to have caused longer‐term changes to disease stage or treatment.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The doubling time of squamous cell carcinoma of the head and neck is short, so delays in diagnosis and treatment increase the risk of upstaging, inoperability, and more complex reconstructive procedures [ 5 , 6 ]. Optimal survival and functional outcomes are achieved with timely multidisciplinary intervention for head and neck cancer (HNC) patients [ 7 ].…”
Section: Introductionmentioning
confidence: 99%